Provision of services to subscribers of optical access networks in the GeoUtr program (MMIT Proceedings, 2025)
For the provision of services to subscribers of optical access networks in the GeoUtr program, JSC “Uzbektelecom”’s optical fiber networks play a key role in the transmission of large amounts of data such as video, audio, and high-speed Internet. They also provide opportunities for further expansion and modernization of the network infrastructure